Extracellular matrix-bound FGF2 mediates estrogen receptor signaling and therapeutic response in breast cancer - DiGiacomo, Josh W. (Mol Cancer Res, 2020)
The extracellular matrix (ECM) is often unaccounted for in studies that consider the stromal contribution to cancer cell signaling and response to treatment. To investigate the influence of a fibrotic microenvironment we utilize fibroblast-derived ECM scaffolds as a cell culture platform. We uncover that estrogen receptor-positive (ER+) breast cancer cells cultured within ECM-scaffolds have an increase in ER signaling that occurs via a MAPK-dependent, but estrogen-independent manner. The ECM acts as a reservoir by binding, enriching, and presenting growth factors to adjacent epithelial cells. We identified FGF2 as a specific ECM-bound factor that drives ER signaling. ER+ cells cultured on ECM matrices have reduced sensitivity to ER-targeted therapies. The sensitivity to ER-targeted therapy can be restored by inhibiting FGF2-FGFR1 binding. ECM-FGF2 complexes promote Cyclin D1 induction which prevents G1 arrest even in the presence of antiestrogens. This work reveals a previously unaccounted for role of the ECM in ER signaling and resistance to endocrine therapy and suggests that patients with ER+ breast cancer that have high mammographic breast density and an intact FGFR signaling pathway may benefit from existing FGFR-targeted therapies.